Molecular identification of T. brucei s.l. in tsetse flies after long-term permanence in field traps - Joana Gomes; Celia Leão; Filipa Ferreira; Maria Odete Afonso; Catarina Santos; Théophile Josenando; Jorge Seixas; Jorge Atouguia; Sonia Centeno-Lima (Journal of Infection in Developing Countries)
Background: Tsetse flies (Glossina spp.) are responsible for the transmission of trypanosomes, agents of animal and Human African Trypanosomiasis (HAT). These diseases are associated with considerable animal and human economical loss, morbidity and mortality. The correct identification of trypanosomes species infecting tsetse flies is crucial for adequate control measures. Identification presently requires technically difficult, cumbersome, and expensive on-site fly dissection. To obviate this difficulty we explored the possibility of correctly identifying trypanosomes in tsetse collected, under field conditions, only for number determination.